2020
DOI: 10.3390/biom10010135
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Mitochondrial Metabolic Reprogramming and Oxidative Stress to Overcome Chemoresistance in Cancer

Abstract: Metabolic reprogramming, carried out by cancer cells to rapidly adapt to stress such as hypoxia and limited nutrient conditions, is an emerging concepts in tumor biology, and is now recognized as one of the hallmarks of cancer. In contrast with conventional views, based on the classical Warburg effect, these metabolic alterations require fully functional mitochondria and finely-tuned regulations of their activity. In turn, the reciprocal regulation of the metabolic adaptations of cancer cells and the microenvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 115 publications
(153 reference statements)
0
39
0
1
Order By: Relevance
“…Moreover, several features of TRAP1 biology and its role in cancer cells are consistent with its function in stemness maintenance. TRAP1 represents a key determinant of cancer cell adaptation to different environmental conditions (i.e., oxidative, endoplasmic reticulum, and metabolic stress), being responsible for protection toward apoptosis, mitochondrial integrity, and drug resistance [ 31 , 32 , 33 ]. TRAP1 is also responsible for reprogramming of tumor bioenergetics as it downregulates oxidative phosphorylation, upon inhibition of succinate dehydrogenase, and enhances Warburg metabolism [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several features of TRAP1 biology and its role in cancer cells are consistent with its function in stemness maintenance. TRAP1 represents a key determinant of cancer cell adaptation to different environmental conditions (i.e., oxidative, endoplasmic reticulum, and metabolic stress), being responsible for protection toward apoptosis, mitochondrial integrity, and drug resistance [ 31 , 32 , 33 ]. TRAP1 is also responsible for reprogramming of tumor bioenergetics as it downregulates oxidative phosphorylation, upon inhibition of succinate dehydrogenase, and enhances Warburg metabolism [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This metabolic rearrangement does not only affect ATP generation, but also supports the biosynthesis of cellular building blocks such as carbohydrates, lipids, proteins and nucleic acids, which are crucial in proliferating cancer cells, [38,39,41]. Changes in mitochondrial oxidative phosphorylation (OXPHOS) are often reported in cancer cells, and OXPHOS related mutations are associated with tumorigenesis [28,31,42,43]. To accommodate the increased glucose dependence, increased expression of several transporter proteins occurs in various cancer types, such as glucose transporter proteins (GLUTs) [44][45][46][47].…”
Section: The Capability Of Malignant Cells To Deregulate Cellular Enementioning
confidence: 99%
“…Increased glycolysis at the expense of mitochondrial respiration, a characteristic feature of aerobic glycolysis, may protect against the production of reactive oxygen species (ROS), as they are by-products of mitochondrial electron transport. Excessive ROS may cause oxidative damage in the cells, and lead to mutations and apoptosis [31,[76][77][78]. It has been suggested that reduced rates of mitochondrial respiration serves a protective function against ROS-induced cell damage, in cancer models of therapy resistance [31,76].…”
Section: The Capability Of Malignant Cells To Deregulate Cellular Enementioning
confidence: 99%
See 2 more Smart Citations